The Effect Of Financial Ratios And Company Size On Audit Report Lag In Food And Beverage Sub-Sector Companies Listed On The Indonesia Stock Exchange - Hafiz, Dinda Maulana; Siregar, Nancy Mayriski (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Audit report lag is the period of audit completion measured from the closing date of the company's books to the date of the audit report. Delays in submitting audit reports can affect the relevance of financial information to stakeholders. This study aims to analyze the influence of financial ratios and company size on audit report lag in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach with multiple linear regression analysis methods. The research population is all food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The sampling technique uses purposive sampling with the criteria of companies that consistently report annual financial statements and have complete data during the research period. Independent variables include return on asset ratio, debt to equity ratio, and company size (natural logarithm total assets). Dependent variables are audit report lag measured in units of days. The results of the study show that partially, the Debt to Equity Ratio has a significant positive effect on audit report lag. Return on Assets has no significant effect on audit report lag. The size of the company has a significant negative effect on audit report lag. Simultaneously, the three independent variables had a significant effect on audit report lag with an F-count value of 15.115 and a significance of 0.000. A determination coefficient (R²) of 0.305 indicates that 30.5% of audit report lag variations can be explained by variables in the model, while the remaining 69.5% are explained by other factors outside the model.